2007
DOI: 10.1007/s10641-007-9252-3
|View full text |Cite
|
Sign up to set email alerts
|

Purification and properties of Sandercyanin, a blue protein secreted in the mucus of blue forms of walleye, Sander vitreus

Abstract: A blue protein present in the mucus coating blue forms of walleye, Sander vitreus, was purified to homogeneity by a combination of ion exchange and hydrophobic interaction chromatography. The purified protein has a molecular mass of 87,850 and is a homotetramer with a subunit molecular mass of 21,836. Solutions of the protein are deep blue in color and show absorbance maxima at 383 and 633 nm, respectively. Acetone treatment of the protein releases a blue chromophore with the spectral characteristics of bilive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…Yu et al (1) have previously reported the purification of the native blue protein from walleye mucus and the partial protein sequence of Sandercyanin, which suggested that it belongs to the lipocalin family of proteins (20,21). They also showed that BLA is noncovalently bound to the protein.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Yu et al (1) have previously reported the purification of the native blue protein from walleye mucus and the partial protein sequence of Sandercyanin, which suggested that it belongs to the lipocalin family of proteins (20,21). They also showed that BLA is noncovalently bound to the protein.…”
Section: Resultsmentioning
confidence: 98%
“…Native Sandercyanin was extracted and purified from the mucus of blue forms of walleye from Northwest Ontario by chromatographic techniques as described previously (1). A putative amino acid sequence of the protein was determined from crystal structure of the native protein, confirmed, and corrected after partial genome sequencing of blue walleye.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations